Study on a modified reactive power allocation strategy of WF management system considering electrical loss reduction and flexibility in practical operation. Issue 5 (8th February 2019) - Yoo, Yeuntae; Lee, Jae‐Hyeong; Jang, Gilsoo; Yoon, Minhan; Jung, Seungmin
Abstract : The recent development of a number of advanced wind farm (WF) operation strategies, using designed verification studies, has resulted in various operational and economic improvements. These applications focused on stabilised conditions to confirm the improved effect derived from a maximum power extraction condition. In the case of large‐scale WFs, however, a physical area with realistic environmental variations should be considered in order to conduct applicable case studies. In this study, the authors propose a modified reactive power allocation strategy, based on proportional techniques, with the system components of a WF structure for utilisation under a variety of practical situations. The proposed method introduces a modified loss prediction model, which takes the resistive components of the wind turbine into consideration. Each analysis is conducted to confirm the feasibility of active reference assignment in terms of loss reduction and flexibility. The simulations are based on electromagnetic transients using DC software tools to perform electrical loss estimation, in order to verify the effectiveness of this strategy.